2021
DOI: 10.1002/tesq.3082
|View full text |Cite
|
Sign up to set email alerts
|

From Crisis to Opportunity: Turning Questions about “Plagiarism” into Conversations about Linguistically Responsive Pedagogy

Abstract: INVITED TEACHING ISSUESTESOL Quarterly welcomes evaluative reviews of publications relevant to TESOL professionals. In addition to textbooks and reference materials, these include computer and video software, testing instruments, and other forums of nonprint materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Thirdly, a large body of academic literature on the issue of plagiarism exists. Other than guidance notes targeting students (e.g., Price, 2014), there are commentaries, discussions and sharing of educational approaches from individual institutions (e.g., Henderson & Whitelaw, 2013;Tomaš & Shapiro 2021), as well as a large body of literature reporting pedagogical interventions or strategies designed to teach students how to avoid plagiarism (e.g., Obeid & Hill, 2017;Perkins et al, 2020;Reyneke et al, 2021). This suggests that specific instruction on how to avoid plagiarism may often be offered at universities (e.g., Elander et al, 2010;Graham et al, 2021).…”
Section: A Systematic and Text-based Specific Approach To Addressing ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, a large body of academic literature on the issue of plagiarism exists. Other than guidance notes targeting students (e.g., Price, 2014), there are commentaries, discussions and sharing of educational approaches from individual institutions (e.g., Henderson & Whitelaw, 2013;Tomaš & Shapiro 2021), as well as a large body of literature reporting pedagogical interventions or strategies designed to teach students how to avoid plagiarism (e.g., Obeid & Hill, 2017;Perkins et al, 2020;Reyneke et al, 2021). This suggests that specific instruction on how to avoid plagiarism may often be offered at universities (e.g., Elander et al, 2010;Graham et al, 2021).…”
Section: A Systematic and Text-based Specific Approach To Addressing ...mentioning
confidence: 99%
“…However, the literature on educational integrity has often adopted a stance of cultural relativism over the issue of plagiarism, speaking of "cultural" attitudes towards textual borrowing and textual ownership. It has often been suggested that students from Confucian-heritage societies hold certain "cultural" values on using prior texts that are at variance with English-L1 (English as the First Language) norms (Amsberry, 2009;Lund, 2004;Sowden, 2005;Tomaš & Shapiro, 2021). We believe "cultural difference" is a complex and tricky notion; as such it has rightly been interrogated by previous researchers from different perspectives.…”
Section: Introductionmentioning
confidence: 96%
“…Gallagher & Haan, 2018;Gallagher et al, 2020;Haan et al, 2017), faculty development of LRI-related pedagogical knowledge (e.g. Zawacki & Cox, 2014;Tomaš & Shapiro, 2021;He & Bagwell, 2022); and international students' experiences with linguistically responsive practices (e.g. Zhang-Wu & Brisk, 2021).…”
Section: Faculty Support For Multilingual Studentsmentioning
confidence: 99%